The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.ultrasmedbio.2006.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Threshold estimation of ultrasound-induced lung hemorrhage in adult rabbits and comparison of thresholds in mice, rats, rabbits and pigs

Abstract: The objective of this study was to assess the threshold and superthreshold behavior of ultrasound (US)-induced lung hemorrhage in adult rabbits to gain greater understanding about species dependency. A total of 99 76 ± 7.6-d-old 2.4 ± 0.14-kg New Zealand White rabbits were used. Exposure conditions were 5.6-MHz, 10-s exposure duration, 1-kHz PRF and 1.1-μs pulse duration. The in situ (at the pleural surface) peak rarefactional pressure, p r(in situ) , ranged between 1.5 and 8.4 MPa, with nine acoustic US expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
2
19
1
3
Order By: Relevance
“…Thus, the mechanical mechanism(s) capable of causing such damage are likely related to the stress that focused ultrasound imposes directly on the lung's air-blood barrier such as radiation forces (Chu and Apfel 1982;Elrod et al 1989). We have shown that the histopathologic characteristics of the gross and microscopic lesions of pulsed ultrasound-induced lung hemorrhage are identical in four species (mice, rats, rabbits and pigs) (O'Brien et al 2006) and that hemorrhage in these species occurs at exposure conditions similar to those used for scanning in human beings. Thus, these findings suggested a common pathogenesis in the initiation and propagation of the lesions at the gross and microscopic levels; however, the exact mechanism of injury remained elusive.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the mechanical mechanism(s) capable of causing such damage are likely related to the stress that focused ultrasound imposes directly on the lung's air-blood barrier such as radiation forces (Chu and Apfel 1982;Elrod et al 1989). We have shown that the histopathologic characteristics of the gross and microscopic lesions of pulsed ultrasound-induced lung hemorrhage are identical in four species (mice, rats, rabbits and pigs) (O'Brien et al 2006) and that hemorrhage in these species occurs at exposure conditions similar to those used for scanning in human beings. Thus, these findings suggested a common pathogenesis in the initiation and propagation of the lesions at the gross and microscopic levels; however, the exact mechanism of injury remained elusive.…”
Section: Introductionmentioning
confidence: 95%
“…The variation in PCH observed with various limited parameter sets have been reviewed by AIUM (2000) and Church et al (2008). Different species have been used in the research, including mice, rats, rabbits, pigs, monkeys and humans (AIUM, 2000; O’Brien et al 2006; Church et al 2008). In addition, biological conditions are important, including age (Dalecki et al 1997; O’Brien et al 2003) and the specific anesthesia techniques (Miller et al 2014a; Miller et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…[11] More importantly, the threshold of all UILH was within the range of diagnostic ultrasound and the mechanism of injury appeared to be specie and age independent; which increases the transposability of these findings to human fetuses. The possibility of a substantial temperature rise in the brain of fetuses when insonated in utero with diagnostic pulsed ultrasound have been demonstrated in guinea pigs, sheep, and human fetuses, [12] thus, again, demonstrating specie independent bioeffect.…”
Section: Bioeffects Of Ultrasoundmentioning
confidence: 91%